2016
DOI: 10.1016/j.matdes.2015.09.162
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model and design of electroadhesive pad with interdigitated electrodes

Abstract: Electric fields alter adhesive forces between materials. Electroadhesive forces have been utilized in diverse applications ranging from climbing robots, electrostatic levitation to electro-sticky boards. However, the design of electroadhesive devices still largely relies on empirical or "trial-and-error" approaches. In this work, a theoretical model is presented to analyze the electrostatic field between the supporting wall and the electroadhesive device with periodic coplanar electrodes. The air-gap between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…The previous theoretical and simulation results have shown that the interfacial electroadhesive force is proportional to the square of the applied voltage. 10,11 The experiment results, especially the results from the recent work by Koh et al, 12 however, have consistently demonstrated the inappropriateness of this pure quadratic relationship. [12][13][14][15] Also, there is a lack of a standardised or recognised experiment setup and procedure to investigate this relationship, especially by taking the surface texture of the interfacial surfaces and environmental factors into consideration.…”
mentioning
confidence: 93%
“…The previous theoretical and simulation results have shown that the interfacial electroadhesive force is proportional to the square of the applied voltage. 10,11 The experiment results, especially the results from the recent work by Koh et al, 12 however, have consistently demonstrated the inappropriateness of this pure quadratic relationship. [12][13][14][15] Also, there is a lack of a standardised or recognised experiment setup and procedure to investigate this relationship, especially by taking the surface texture of the interfacial surfaces and environmental factors into consideration.…”
mentioning
confidence: 93%
“…The electroadhesive force can be derived by the Maxwell stress tensor method [13][14][15][16][17][18]21]. We calculate the electroadhesive force between the two solids when the surfaces are separated by a distance u (see Fig.…”
Section: Electroadhesion With a Constant Air-gapmentioning
confidence: 99%
“…In these cases the adhesive pad must be built from an elastically soft material in order to increase the contact area and hence the friction force. Modeling of electroadhesive forces has been based on the parallel-plate-capacitor structure [12][13][14][15] when an electroadhesion pad is contacting a conductive or semiconductive substrate material, and the coplanar-platecapacitor structure [16][17][18] when an electroadhesion pad is contacting an insulating substrate material.…”
Section: Introductionmentioning
confidence: 99%
“…8 Electroadhesion is an electrically controllable and dynamic 8 electrostatic attraction between an electroadhesive pad and a substrate, with 33 variables influencing the interfacial electroadhesive force. 9 These variables include voltage 10,11 and material properties such as relative permittivity, [10][11][12] pad geometry, 13,14 surface texture, 15 and environmental conditions. 9,16 A typical electroadhesion system contains four main parts, including an electroadhesive pad, a power supply, a control system, and a substrate, as can be seen in Fig.…”
mentioning
confidence: 99%